ENHANCING SUSTAINABILITY THROUGH IDEAS, CREATIVITY, SCIENCE AND TECHNOLOGY – USM LAUNCHES IDEA BANK - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, May 2015 Creativity and ideas are important elements that can ensure the sustainability of arts and culture in the face of modernday challenges. The ViceChancellor of Universiti Sains Malaysia (USM) Professor Dato’ Dr. Omar Osman stressed that martial arts was an example of a universal art form symbolising its founding ethnic group’s sovereignty besides being an example of local wisdom that ought to be highlighted, strengthened and continuously adapted to face future developments and challenges in the effort to mould holistic graduates as aspired to in the Malaysian Higher Education Development Plan.